Reducing Mortality in AIS Patients After EVT: Challenges and Prospective Strategies [Letter] - Lu Y; Weng L; Zhou T (Clinical Interventions in Aging)
Yuqiu Lu,1 Lingtian Weng,2 Tianmei Zhou3 1The Second School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People’s Republic of China; 2The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People’s Republic of China; 3Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Tianmei Zhou, Tongde Hospital of Zhejiang Province, Gucui Road No. 234, Hangzhou, Zhejiang Province, People’s Republic of China, Tel +8613388617507, Email ztm729@126.com